Smart Design First International Conference Proceedings - Breedon, Philip; SpringerLink (Online service) (London : Springer London, 2012)
Good product designs merge materials, technology and hardware into a unified user experience; one where the technology recedes into the background and people benefit from the capabilities and experiences available. By focusing on functional gain, critical awareness and emotive connection, even the most multifaceted and complex technology can be made to feel straightforward and become an integral part of daily life. Researchers, designers and developers must understand how to progress or appropriate the right technical and human knowledge to inform their innovations. The 1st International Smart Design conference provides a timely forum and bring together researchers and practitioners to discuss issues, identify challenges and future directions, and share their R&D findings and experiences in the areas of design, materials and technology. This proceedings of the 1st Smart Design conference held at Nottingham Trent University in November 2011 includes summaries of the talks given on topics ranging from intelligent textiles design to pharmaceutical packaging to the impact of social and emotional factors on design choices with the aim of informing and inspiring future application and development of smart design.
Foreword -- 1. Rethinking packaging: how electronic packs for pharmaceuticals work with mobile IT to improve patient adherence to medication regimens -- 2. The four horsemen: the evolution of science and society -- 3.Changing the fabric of society: an exploration of smart textiles in product design -- 4. Smart housing: an intelligent environment for aging independently -- 5. Enhancing visibility in bicycling apparel using integrated flashing LEDs -- 6. Hydrophobic smart material for water transport and collection -- 7. Intelligent housing for people and technology: examining sustainable housing beyond the technical and the opportunities for design -- 8. Interrogating hyperfunctionality -- 9. Semefulness: touch, design and meaning -- 10. Conceptualisation of an intelligent salutogenic room environment -- 11. Development and thermographic analysis of custom seats for wheelchairs -- 12. Designing a knit methodology for technical textiles -- 13. Soft products: Smart Fabrics in product design -- 14. Autonomous mobility scooter as an assistive outdoor tool for the elderly -- 15. Emotional Design: understanding immaterial values for the development of products.
Keywords: Engineering; Architectural design; Engineering design; Structural control (Engineering).; Engineering; Engineering Design; Industrial Design; Operating Procedures, Materials Treatment; Interaction Design